Economic Perspectives on Craft Beer A Revolution in the Global Beer Industry (Springer International Publishing, 2018)
This book investigates the birth and evolution of craft breweries around the world. Microbrewery, brewpub, artisanal brewery, henceforth craft brewery, are terms referred to a new kind of production in the brewing industry contraposed to the mass production of beer, which has started and diffused in almost all industrialized countries in the last decades. This project provides an explanation of the entrepreneurial dynamics behind these new firms from an economic perspective. The product standardization of large producers, the emergence of a new more sophisticated demand and set of consumers, the effect of contagion, and technology aspects are analyzed as the main determinants behind this 'revolution'. The worldwide perspective makes the project distinctive, presenting cases from many relevant countries, including the USA, Australia, Japan, China, UK, Belgium, Italy and many other EU countries.